(untitled) (Economics and region, 2017)
UDC 331.526 Svitlana Ivanytska, PhD (Economics), associate professor, Tetiana Halaida, senior lecturer. Poltava National Technical Yuri Kondratyuk University. Analysis of structural changes of employment in Poltava and Poltava region by economic activities. The article investigates the factors of influence on the change in the structure of employment of the population. It was revealed that in the past decade a number of important changes took place in the structure of employment by economics sectors, the most significant is the excess of the share of employed in the services sector over the share of employed in the agricultural and industrial sector, which is due to the impact of socioeconomic transformations in the economy, politics, the legal sphere and in society in general. The analysis of the sectoral employment structure of the population in Poltava region and in Poltava town is done. The tendencies characterizing such aspect of regional and local labor markets as employment in the context of types of economic activity are revealed. During the 2013-2015 the largest in the region remains the number employed in the sectors agriculture, forestry and fisheries, industry, wholesale and retail trade; repair of motor vehicles and motorcycles. The smallest numbers of employees are in the sectors information and telecommunications, art, sport, entertainment and recreation. There is a decrease in the share of employed in industry and an increase in the share of employed in education, health and public administration, defense and social insurance of the population, art, sports and entertainment and recreation. It was revealed that the share of people employed in construction, catering, information and telecommunications, financial and insurance activities, as well as in the provision of other types of services is much larger in the city of Poltava than in the region in general. The directions of using the complex of economic, financial and social measures at the local and regional levels as well as systematically monitoring changes in the sectoral structure of employment at the regional and local levels with the aim of timely responding to modern challenges are proposed. Keywords: employment, employment structure of the population, labor market, staff employees, labor force, hidden unemployment.